Терапевтична ефективність дієтичних добавок Фітосил-С та Фітосил-С+ при лікуванні синдрому залежності від алкоголю, спричиненого посттравматичним стресовим розладом - Postrelko, V. M.; Barvinchenko, V. M.; Lipkovska, N. O.; Kartel, M. T. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2017)
Dietary supplements Phytosil-S that contains the enterosorbent Silics and dispersed medicinal plants (hawthorn flowers, motherwort grass, melissa herb, thyme grass), and Phytosyl-S+, which further includes hop stems (cones) were developed. Their high therapeutic efficacy in the treatment of alcohol dependence syndrome caused by posttraumatic stress disorder was detected on the example of participants of anti-terrorist operation in the East of Ukraine. No contraindications, side effects and allergic reaction were found.